Dispersion and evaporation of droplets amended with adjuvants on soybeans - Gimenes, M. J.; Zhu, H.; Raetano, Carlos Gilberto [UNESP]; Oliveira, R. B. (Elsevier, 2013)
Quantification of the effects of adjuvants on droplet behaviour on plant surfaces is needed to improve pesticide spray application efficiency for soybeans. Dispersion and evaporation of single 300-μm diameter droplets amended with each of four spray adjuvants at five concentrations were investigated for four soybean plant surfaces (abaxial and adaxial leaflet surfaces, petiole, basal stem). The four adjuvants were a crop oil concentrate (COC), a modified seed oil (MSO), a non-ionic surfactant (NIS) and an oil surfactant blend (OSB). A single-droplet generator was used to produce and deposit 300-μm diameter droplets on target surfaces under controlled environmental conditions. Adjuvants significantly increased the dispersion (or wetted area) of droplets on plant surfaces. Droplet-wetted areas increased with increased adjuvant concentrations but not in direct proportion. The average increases of wetted areas across the four soybean plant surfaces were 443, 462, 416, or 343% when the spray mixture was amended with COC, MSO, NIS or OSB at the manufacturer-recommended concentrations, respectively. Among the four surfaces, the largest wetted area was on the abaxial surface, followed by the adaxial surface, the petiole and then the basal stem. Droplet evaporation times were inversely proportional to the wetted areas. The evaporation time of 300-μm diameter droplets ranged from 36 to 142. s on the four surfaces when the spray mixture was amended with an adjuvant, whereas the water-only droplets ranged from 161 to 190. s. The results demonstrated that use of adjuvants offers great potential to improve the homogeneity of sprayed pesticides, to increase spray coverage and to reduce pesticide application rates on soybean plants. These effects could benefit farmers economically and reduce environmental contamination by pesticides. © 2012.
Keywords: Evaporation time; Formulation; Spray coverage; Spray deposition; Surfactant; dispersion; droplet; evaporation; integrated pest management; pesticide application; quantitative analysis; soybean; surfactant; Glycine max